Representation of Women's Beauty in Garnier Advertisements Light Complete Brightening Foam - Cornellia Yulin Esther Dita; Farid Pribadi (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2022)
Beauty is an important thing for a woman because beauty describes the quality of a woman. In our daily life, we often encounter several advertisements that represent the beauty of a woman, one of which is the Garnier Light Complete Brightening Foam advertisement. Representation is a picture that has a certain meaning, so that everyone can have a different understanding in interpreting an action. In this article, we will discuss the representation of women's beauty in Garnier Light Complete Brightening Foam advertisements because the purpose of writing this article is to examine more deeply about the representation of women's beauty in advertisements that can affect consumer interest in consuming a product. In this Garnier Light Complete Brightening Foam advertisement, a woman who has a dull face is depicted and uses products from Garnier Light Complete Brightening Foam so that she has a bright face. This study is interested in reading the representation of beauty in the Garnier Light Complete Brightening Foam advertisement using an interpretive qualitative approach with semiotic textual analysis. In this study, the semiotic theory of Roland Barthes is used to reveal the meaning of the picture of beauty expressed by the Garnier Light Complete Brightening Foam advertisement video. The results of this study indicate that in the advertisement it is explained that beauty is a very important thing for every woman to have. Women will be much happier if they have a clean and bright face.